1. ## Functions

1. H function given by H(t)= -1
Find
a) H(0); b) H(x+h), c) H(3t); d) H(t+2) - H(t)

2. Given the functions f(x)=3/x^2 - 4 and g(x)=x-2
Find
a) f(x) -g(x) b) f(x)g(x) c) f(x)/g(x)

Thanks a lots.

2. Originally Posted by Trigon
1. H function given by H(t)= -1
Find
a) H(0); b) H(x+h), c) H(3t); d) H(t+2) - H(t)

2. Given the functions f(x)=3/x^2 - 4 and g(x)=x-2
Find
a) f(x) -g(x) b) f(x)g(x) c) f(x)/g(x)

Thanks a lots.
What have you tried? Where are you stuck?

3. Originally Posted by mr fantastic
What have you tried? Where are you stuck?
Q 1. I have no idea at all. I am guessing H(0)= -1 but why I do not know?

Q 2. I tried a/b-c/d= ad-bc/ad etc but nothing more.

4. Originally Posted by Trigon
Q 1. I have no idea at all. I am guessing H(0)= -1 but why I do not know?

Q 2. I tried a/b-c/d= ad-bc/ad etc but nothing more.
Q1. H(t) is a constant function. It's equal to -1 for all values of t.

Q2. Substitute the given rules for f(x) and g(x) into each expression. Simplify where appropriate.